The impact of the international rice genebank’s (IRG) on rice farming in Bangladesh - Donald Villanueva; Yuji Enriquez; Grace Lee Capilit (CABI Agriculture and Bioscience)
Abstract Background The International Rice Genebank (IRG) currently safeguards the largest and most diverse collection of rice genetic resources in the world. Over the past decades, genetic resources from the IRG have been used effectively to increase smallholder farmers’ rice productivity in developing economies. Bangladesh is one of the direct and indirect recipients of IRG germplasm for rice genetic improvement. This study aimed to map the impact pathways of IRG germplasm transfers to Bangladesh, evaluate the genetic contribution of IRG germplasms to rice productivity of farmers, and compute the equivalent economic benefit. Methods Impact pathway analysis was conducted to map the IRG’s germplasm transfer for varietal improvement and seed dissemination of improved rice varieties in Bangladesh using the information collected from key informant interviews. Using data from the farm household survey conducted by the International Rice Research Institute (IRRI) in 2016 in five divisions in Bangladesh, a pedigree analysis was conducted that related the productivity changes in farmers’ fields explicitly to genebank accessions through varietal improvement. Afterward, we evaluated the economic benefit of IRG contribution in rice varietal improvement in Bangladesh using the computed marginal increases in productivity, average paddy price, and estimated total rice area. Results IRG’s impact pathway on germplasm transfer in Bangladesh showed that impacts for farmers were achieved through joint efforts with IRRI and the National Agricultural Research and Extension System’s research-for-development programs. On average, 52% of the improved rice varieties’ genetic composition, cultivated by farmers in Bangladesh, definitely came from IRG accessions. This contribution factor could increase up to 67% if possible contributions were taken into account. The results of the Cobb–Douglas model implied that for every 1% increase in the definite IRG contribution to an improved rice variety, there was an increase in rice yield of about 0.99%, holding other factors constant. This yield increase can be translated into an additional US$ 8,576,973 aggregated net benefit of farmers during the wet season in Bangladesh. The enhanced yield can be associated with the added important agronomic traits contributed by the accession provided by the IRG in the genetic background of the rice varieties developed for farmers in Bangladesh. Conclusions The findings of the study demonstrate that IRG accession forms a significant part of the ancestry of improved rice varieties which is associated with improved yield. The study highlights the valuable contribution of IRG’s conservation and distribution of genetic accessions to the research and development of improved rice varieties and rice production on farms in Bangladesh.